BRICKS COUNTING FROM AN IMAGE USING IMAGE PROCESSING - Gayatri Dixit1 , Supriya Kodag2, Supriya Jadhav3, Bhagyashree Waghmode4, Kalpana Swami5 (International Journal of Innovations in Engineering Research and Technology, 2022)
Construction progress is predominantly measured with manual site surveys. These surveys are labor-intensive, on-site manual investigations. The generated survey reports are subjective and approximate because they are based on the surveyors’ individual experiences. The “Counting bricks in an image using python” this project helps us to prevalent method of measuring progress is through manual site surveys. The prevalent method of measuring progress is through manual site surveys. These surveys are tedious and time consuming. They are also approximate, as counting the number of bricks in-place to compare against those ordered is a very laborious task compared to its end value. In previous research, we are able to count the number of bricks using single images. This paper presents a method for counting bricks in-placed to automate the brick site survey using image processing. This method improves the brick counting method on image to a continuous counting in image. It can compare the brick detection results in successive frames and accumulate the counts when new bricks appear. The method works by the following two steps. (1) Count the number of bricks in an image. and add new bricks to the count upon the appearance in an image. This paper also demonstrated a performance comparison of traditional brick counting approach and automated counting approach. Test results demonstrate that this method is capable of counting the number of bricks in an image with acceptable error.